MENCIPTAKAN RUANG AMAN BAGI AUDITOR DALAM PENGAMBILAN KEPUTUSAN ETIS - Reza Ramadhania; Satya Fauziah (RISTANSI: Riset Akuntansi, 2025)
This study aims to understand how organizational culture influences auditors’ professional courage when facing ethical pressures in audit practice. Auditors’ moral courage is essential for maintaining integrity and objectivity, especially when confronted with ethical dilemmas that may threaten the credibility of the profession. An organizational culture that emphasizes transparency, accountability, and ethical leadership is believed to strengthen such courage, whereas a hierarchical, closed, and unsupportive culture toward ethical reporting may weaken auditors’ courage and encourage dysfunctional behavior. This study employs a qualitative approach with an interpretive paradigm, aiming to explore the subjective meanings behind auditors’ experiences when dealing with ethical dilemmas. Data were collected through in-depth interviews with auditors working at Public Accounting Firms (KAP) in East Java. The findings indicate that auditors’ ethical courage is shaped by three key factors: organizational culture, authentic leadership, and the ethical climate within the workplace. These factors interact to form a value system that either supports or inhibits auditors in making independent and ethical decisions. This study provides a comprehensive understanding of how these organizational factors influence auditors’ professional courage and offers recommendations for creating a work environment that promotes ethical and independent decision-making in audit practice.